Patient-Reported Outcome Measures for Patients Undergoing Inguinal Hernia Repair - Gram-Hanssen, Anders; Tolstrup, Anders; Zetner, Dennis; Rosenberg, Jacob (Frontiers in Surgery, 2020)
There are many ways to determine the success of an inguinal hernia operation. Traditional measures are hernia recurrence, neuralgia, mesh infection, or rather the absence of these complications. While these traditional measures obviously have their merits, alternative outcomes are emerging, and researchers and clinicians are gaining an increasing interest in patient-reported outcomes and Patient Reported Outcome Measures (PROMs). PROMs are patient questionnaires concerning quality of life, chronic pain, disability, or other subjects that are best assessed by the patients. PROMs come in two different forms: generic and condition-specific. The generic PROMs concern general symptoms and issues, while the condition-specific PROMs target patients with a certain condition. Inguinal hernia-specific PROMs typically address issues like mesh-related symptoms, groin pain, sexual dysfunction, etc. Clinical measurement instruments such as PROMs should be carefully validated according to standardized guidelines to ensure their psychometric measurement properties. Unfortunately, this type of evidence is often lacking when it comes to inguinal hernia-specific PROMs. In this review, we explain why PROMs are useful for patients with inguinal hernia, and why one should use inguinal hernia-specific PROMs as opposed to the generic ones. We address the importance of population-specific validation, and explain what type of evidence is lacking. Lastly, we discuss the future prospects of using PROMs for patients with inguinal hernia.